State Management in Times of Crisis: Perception of the Government’s Policy of Counteracting the COVID-19 Pandemic in Poland - Szostak, Maciej; Olszanecka-Marmola, Agata (Political Preferences, 2022)
The COVID-19 pandemic has brought entirely new challenges to state crisis management. Until then, none of the governments had faced the need to stop almost all social and economic life. The fight against the pandemic required the introduction of numerous restrictions limiting mobility and interpersonal contacts. Initially, people did not widely deny their necessity, but over time parts of society protested increasingly against further restrictions. In this article, we check whether party preferences and socio-demographic features influenced the assessment of the Polish government's actions to counter the pandemic's spread. For this purpose, we develop a 10-item anti-COVID-19 activity (ACA) scale consisting of a general assessment of COVID-19 counteracting activity and evaluation of its various dimensions (e.g., online education, health care system, vaccination system and help for entrepreneurs). The research confirms a significant difference in how government activities are perceived in relation to political preferences and gender. The study participants negatively assessed the anti-COVID policy. Furthermore, men and voters of the Confederation turned out to be particularly unfavorable to the government's actions.